2005
DOI: 10.1093/chemse/bji050
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Flavor Labeling and Flavor Recall Ability in Children

Abstract: This study sought to determine if the ability to label a flavor is associated with an improved ability to recall having tasted the flavor in preschool-aged children. A total of 120 3- to 6-year-old English-speaking children tasted and labeled 20 different flavors, blinded to color. Children's labels for the flavors were scored for consistency and accuracy. Recall for having tasted the flavor was tested. Both labeling ability and recall ability improved rapidly between the ages of 3 and 6 years in this cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
2
18
1
4
Order By: Relevance
“…The six 'palatable' flavors (apricot, berry blue, Dr. Pepper, grape, kiwi, and plum) were identified from 50 commercially available flavors based on ratings in prior work with the same age range involving 166 children, each of whom tasted 20 different jelly bean flavors (Lumeng & Cardinal, 2007;Lumeng, Zuckerman, Cardinal, & Kaciroti, 2005). The six 'unpalatable' flavors (dirt, garlic, mango, sardine, spaghetti, and spinach) were selected from a line of 14 commercially available novelty jelly beans intended to elicit disgust reactions from children (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The six 'palatable' flavors (apricot, berry blue, Dr. Pepper, grape, kiwi, and plum) were identified from 50 commercially available flavors based on ratings in prior work with the same age range involving 166 children, each of whom tasted 20 different jelly bean flavors (Lumeng & Cardinal, 2007;Lumeng, Zuckerman, Cardinal, & Kaciroti, 2005). The six 'unpalatable' flavors (dirt, garlic, mango, sardine, spaghetti, and spinach) were selected from a line of 14 commercially available novelty jelly beans intended to elicit disgust reactions from children (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Parents of children in our two prior studies using jelly beans as stimuli with children drawn from the same population were queried regarding their child's familiarity with jelly beans. The vast majority of parents reported that their child had previously eaten jelly beans (Lumeng & Cardinal, 2007;Lumeng et al, 2005). Children tasted one quarter of each jelly bean.…”
Section: Methodsmentioning
confidence: 99%
“…Although the implicit nature of food memory is evident, most of the available studies in this field deal with conscious and intentional mechanisms of learning. As regarding children, studies are focused on explicit paradigms to investigate the relationship between flavor labeling and recognition (Frank, Brearton, Rybalsky, Cessna, & Howe, 2011;Lumeng, Zuckerman, Cardinal, & Kaciroti, 2005). However, this approach is reductive as it does not take into consideration the incidental component of memory processes and the understanding of food memory under natural conditions.…”
Section: Implicit Paradigms To Study Food Memory In Childrenmentioning
confidence: 99%
“…Gracias a la interacción preliminar con sus responsables, pudo verificarse que los niños y niñas no padecieran de ningún problema crónico de alimentación o bien alguna restricción médica que les impidieran participar en las pruebas (Birch y Fisher, 2000;Fischer, Mitchell, Smiciklas-Wright y Birch, 2002). Quienes tuvieron un historial médico de desórdenes alimenticios, psicomotores o problemas de expresión se excluyeron del estudio (Lumeng, Zuckerman, Cardinal y Kaciroti, 2005). Fue también necesario que los niños y niñas se hallaran disponibles en el horario requerido, y que estuviesen dispuestos a ser evaluados sin la presencia de sus familiares (Chen, Resurrección y Paguio, 1996;Cartín, 2005).…”
Section: Localización Del Estudio Y Población Involucradaunclassified
“…Antes de realizar las evaluaciones sensoriales y cognitivas con las personas menores, los investigadores se capacitaron en las metodologías y objetivos de las evaluaciones a aplicar antes del inicio de la etapa experimental (Lumeng et al, 2005). Finalizado este proceso, se llevó a cabo una semana de familiarización: las investigadoras tenían el objetivo de entablar relaciones positivas con la población infantil que sería parte del proceso, de modo que se generara un ambiente de confianza que favoreciera su participación activa (Kimmel, Sigman-Grant y Guinard, 1994;Popper y Kroll, 2003).…”
Section: Procedimientos Preliminares a La Evaluación Sensorial Y A Launclassified